Guidance and counseling program for religious awareness in Elderly Islamic Boarding Schools - Hapsari, Lisning Sri; Rahman, Imas Kania; Alim, Akhmad (Tawazun: Jurnal Pendidikan Islam, 2023)
This research aims to examine and formulate guidance and counselling programs for religious awareness at Al-Hikmah Cibungbulang Islamic Boarding School in Bogor and formulate guidance and counselling programs for older people in Islamic boarding schools and social institutions. The research method used is a literature study with a qualitative approach, research and development (R&D) and field methods. This research involved interviews with the head of the foundation, administrators, and elders at Graha Sasana Tresna Werdha House Cibubur East Jakarta for data comparison. An analysis was conducted of the religious awareness guidance and counselling programme at the boarding school for elderly students, as well as formulating a programme that includes daily, weekly, monthly, and annual programmes. The results of this research will be implemented in the form of a systematic and complete theory according to the Educational Counsellor Competency Standards (SKKPD). Hopefully, this research can provide solutions and references for Islamic boarding schools and social institutions in developing practical guidance and counselling programs for older people, especially in the Cibungbulang area of Bogor. Abstrak Penelitian ini bertujuan untuk mengkaji dan merumuskan program bimbingan dan konseling kesadaran beragama di Pondok Pesantren Al Hikmah Cibungbulang Bogor serta merumuskan program bimbingan dan konseling bagi lansia di pondok pesantren dan panti sosial. Metode penelitian yang digunakan adalah studi kepustakaan dengan pendekatan kualitatif, research and development (R&D) serta metode lapangan. Penelitian ini melibatkan wawancara dengan ketua yayasan, pengurus, dan sesepuh di Rumah Werdha Graha Sasana Tresna Cibubur Jakarta Timur sebagai perbandingan data. Analisis dilakukan terhadap program bimbingan dan konseling kesadaran beragama di pondok pesantren untuk lansia, serta merumuskan program yang meliputi program harian, mingguan, bulanan, dan tahunan. Hasil penelitian ini akan diimplementasikan dalam bentuk teori yang sistematis dan lengkap sesuai Standar Kompetensi Konselor Pendidikan (SKKPD). Diharapkan penelitian ini dapat memberikan solusi dan acuan bagi pondok pesantren dan lembaga sosial dalam menyusun program bimbingan dan konseling yang efektif bagi lansia, khususnya di wilayah Cibungbulang Bogor.